Load flow method using genetic algorithm - Lok, C. W.; Zin, A. A. M.; Mustafa, M. W.; Lo, Kueiming Lun (2003)
Genetic algorithms (GAs) are search methods based on the natural selection and natural genetics, while power flow studies, commonly known as load flow, form an important part of power system analysis. This paper presents the implemention of the simple genetic algorithm and constrained genetic algorithm to solve the load flow problem. It compares the performance of the simple genetic algorithm (SGA) and the constrained genetic algorithm (CGA) to solve the load flow problem. Numerical results on two test systems are presented.